Public and private investments for banana Xanthomonas Wilt control in Uganda: The economic feasibility for smallholder farmers - Gotor, Elisabetta; Cori, Viola di; Pagnani, Tiziana; Kikulwe, Enoch Mutebi; Kozicka, Marta; Caracciolo, Francesco (Informa UK Limited, 2022)
Banana Xanthomonas Wilt (BXW) poses a serious threat to livelihoods and food security for millions of households in Africa. Despite considerable investments in Uganda by the Government and other national and international stakeholders, the disease persists in the country after periods of significant resurgence. Building on the Agricultural Innovation Systems framework, this paper reviews the role of the major stakeholders involved in controlling the disease in Uganda. Next, using household survey data, it analyzes economic costs and benefits of adopting an integrated BXW control package for the Ugandan smallholder farmers. After 2015, there has been a significant reduction in both public and private investments in BXW management, which may contribute to future disease resurgence. Our analysis reveals a high level of partial adoption of BXW recommended practices, and just a third of farmers adopting a full control package. This means significant economic losses for non- adopters, as indicated by our findings that households adopting the full package registered a net balance of US$65 per acre higher than non-adopters. We find that disproportionally large costs need to be borne at the beginning of the process, while the benefits are distributed over time, which may present a barrier to adoption by resource-poor smallholders.